A decentralised public key infrastructure for customer-to-customer e-commerce. (2nd May 2005) - Aberer, Karl; Datta, Anwitaman; Hauswirth, Manfred
The success story of eBay has shown the demand for customer-to-customer (C2C) electronic commerce. eBay is a centralised infrastructure with all its scalability problems (network bandwidth, server load, availability, etc.). In this paper, we argue that C2C e-commerce is an application domain that maps naturally onto the emerging field of peer-to-peer (P2P) systems simply by its underlying interaction model of customers, i.e., peers. This offers the opportunity to take P2P systems beyond mere file sharing systems into interesting new application domains. The long-term goal would be to design a fully functional decentralised system which resembles eBay without eBay's dedicated, centralised infrastructure. Since security (authenticity, non-repudiation, trust, etc.) is key to any e-commerce infrastructure, our envisioned P2P e-commerce platform has to address these security issues adequately. As the first step in this direction, we present an approach for a completely decentralised P2P public key infrastructure (PKI) which can serve as the basis for higher-level security service. We base it on a statistical approach and present an analytical model to quantify its behaviour and properties and to provide probabilistic guarantees. To justify our claims, we provide a first-order analysis and discuss the PKI's resilience against various known threats and attack scenarios.